Tree nuts : composition, phytochemicals, and health effects - Alasalvar, Cesarettin; Shahidi, Fereidoon , 1951- (Nutraceutical science and technology, 2009)
Nuts have been long perceived as a high-fat, high-calorie food, best avoided or consumed in moderation. Nuts also provide essential nutrients such as magnesium, chromium, zinc, and manganese. Like all plant foods they are high in fiber and phytochemicals. This book examines popular tree nuts and describes each nut's compositional characteristics.